PENGARUH RASA MANFAAT DAN KEMUDAHAN TERHADAP MINAT BERPERILAKU (BEHAVIORAL INTENTION) PARA MAHASISWA DAN MAHASISWI DALAM PENGGUNAAN INTERNET - I Putu Sugiartha Sanjaya (KINERJA, 2005)
Davis’ Technology Acceptance Model (TAM), perceived usefulness, and perceived ease of use instruments are widely accepted in information technology research community as tools for evaluating information system application and predicting usage. This study attempts to investigate whether perceived usefulness and perceived ease of use influence behavioral intention in using Internet. Perceived usefulness is the degree to which a person believes that using a particular system would enhance his or her job performance. Perceived ease of use is the degree to which a person believes that using a particular system would be free of effort. Data were collected from 149 students of Department of Informatics Technology, Faculty of Industrial Technology, University of Atma Jaya Yogyakarta. The result is that perceived usefulness has a positive and significant influences on behavioral intention, while the influence of perceived ease of use on behavioral intention is not statistically significant.Keywords: perceived usefulness, perceived ease of use, technology acceptance modelbehavioral intention